2005
DOI: 10.1002/pbc.20706
|View full text |Cite
|
Sign up to set email alerts
|

Low incidence of sepsis due to viridans streptococci in a ten‐year retrospective study of pediatric acute myeloid leukemia

Abstract: The low rate of VGS and enterobacteriaceae sepsis was probably due to the effective decontamination. Our supportive care strategy could potentially help enhance overall survival in children with AML.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 34 publications
2
18
0
Order By: Relevance
“…38,39 Implementation of supportive care strategies such as decontamination of gums and gastrointestinal tract has reportedly decreased the incidence of VGS bacteremia. 40 Although an increase of GPC bacteremia on quinolone prophylaxis has not been found by all, 5,17 prophylaxis directed against Gram-negative infections (ie, with quinolones) has been identified as a risk factor for infections with VGS. 22,28,[41][42][43][44] We found that CPx was effective in decreasing aminoglycoside use, most likely because the incidence of GNR infections was lower.…”
Section: Discussionmentioning
confidence: 99%
“…38,39 Implementation of supportive care strategies such as decontamination of gums and gastrointestinal tract has reportedly decreased the incidence of VGS bacteremia. 40 Although an increase of GPC bacteremia on quinolone prophylaxis has not been found by all, 5,17 prophylaxis directed against Gram-negative infections (ie, with quinolones) has been identified as a risk factor for infections with VGS. 22,28,[41][42][43][44] We found that CPx was effective in decreasing aminoglycoside use, most likely because the incidence of GNR infections was lower.…”
Section: Discussionmentioning
confidence: 99%
“…5 Similarly, a single institution study found that 5 (6.4%) of 78 of their children with AML died of infection. 6 The reason for higher infection-related mortality on CCG 2961 may be related to the intensely myelosuppressive nature of this chemotherapy regimen. Alternatively, in intensive Other enterobacteriaceae For personal use only.…”
Section: Discussionmentioning
confidence: 99%
“…Each febrile episode requiring hospitalisation and empiric intravenous antibiotic therapy was counted as a separate infection and categorized as a bloodstream infection (BSI), local infection, or fever of unknown origin (FUO). Bloodstream infections were defined as fever with at least one positive blood culture of bacteria or fungi 18. Multiple organisms from the same patient within the same treatment block were considered separate infections, except for polymicrobial bloodstream infections, which were defined as two or more microorganisms isolated from a single blood culture 19.…”
Section: Methodsmentioning
confidence: 99%